Georaphic Information System of Land Suitablility for Commodities Featured in Sawang District North Aceh - Ari Saptari, Mochamad; Trisna, Trisna (Malikussaleh University, Aceh, Indonesia, 2022)
Actually, Â Sawang is the largest sub-district in North Aceh, Â±38,465 ha or 11.67% of the total area of North Aceh. Consists of thirty nine villages. 3,449 ha are paddy fields and 35,016 ha are non-paddy fields. The use of non-rice field land is usually used by the surrounding community for gardens, forests, and ponds of 27,997 ha. In order to support government programs in improving people's welfare and creating job opportunities, it can be done by developing the potential of agriculture and plantations. Therefore, integrated and complete information is needed regarding the characteristics of land in North Aceh, especially Sawang Sub - District, which is suitable for planting certain types of plants in support of optimal and sustainable land use policies. The purpose of this study is to analyze the nature of the land that is suitable for use as an agricultural area or plantation of superior commodities. The specific purpose of the research is to provide recommendations to local governments to determine policies for the use of vacant land with appropriate plant types. The research steps include preliminary studies, identification of superior commodities, mapping of vacant land, testing of land suitability parameters, determination of land suitability, policy recommendations. Based on the results of the research that has been carried out, the researchers conclude that cocoa is considered the most appropriate plant among several other options, referring to the results of several parameters and observations that have been made, either through spatial studies based on mapping techniques, using special software, or the study of chemical elements, as a support for plant growth, through the results of laboratory tests that have been carried out by the research team.